Enhancing Speaking Proficiency and Learning Motivation through Integrated Active Learning Tasks in Secondary EFL Classrooms - Rampeng; Sujariati; Risman Wanci (Universitas Hamzanwadi, 2026)
Speaking proficiency in EFL classrooms requires more than linguistic knowledge; it depends on sustained opportunities for interaction, participation, and meaningful language use. This study investigated the effects of integrated active learning tasks on secondary students’ speaking proficiency and learning motivation in Indonesian EFL classrooms. Using a quasi-experimental sequential explanatory mixed-methods design, the study included 60 students from two state senior high schools in Makassar, Indonesia, who were divided into an experimental group and a control group. The experimental group received integrated active learning tasks, including role-plays, problem-solving discussions, peer interviews, project-based presentations, and reflective group activities. In contrast, the control group received conventional teacher-centered instruction. Data were collected through speaking pre- and post-tests, a motivation questionnaire, classroom observations, semi-structured interviews, and teaching materials. Quantitative data were analyzed using descriptive statistics, paired and independent-sample t-tests, effect sizes, and correlation analysis, while qualitative data were analyzed thematically. The findings showed that the experimental group achieved substantial improvement in speaking proficiency, particularly in fluency, vocabulary use, and overall performance. Motivation also increased significantly, with the strongest gains in task engagement and intrinsic motivation. Classroom observations and interviews revealed higher participation, more balanced peer collaboration, increased target-language use, and stronger reflective engagement. Positive correlations between motivation and speaking gains further indicated that students who became more motivated and engaged tended to show greater improvement in speaking. These findings suggest that integrated active learning tasks can transform speaking instruction from teacher-dominated performance practice into a more participatory, motivating, and communicative learning process.